Muslim secular democracy voices from within - Lily Zubaidah Rahim 1960- (Palgrave Macmillan, 2013)
The book offers a nuanced and innovative analyses of the emergence of an inclusive secular democratic state paradigm which incorporates the sacred within the framework of secular democracy in the Muslim World.